From Milah (Circumcision) to Milah (Word): Male Identity and Rituals of Childhood in the Jewish Ultraorthodox Community - Bilu, Yoram (Ethos, 2003)
In contemporary Jewish ultraorthodox communities, most three-year-old male children undergo a twofold ritual sequence in which the first haircut is associated with entering the world of study. Focusing on the paramount value of holy Torah study and its prerequisites, I seek to decode the psychocultural meanings of the haircutting and school initiation ceremonies and their ceremonial antecedent, circumcision, as markers on the male trajectory from milah (circumcision) to milah (word). The ritual sequence is evaluated comparatively against the widespread conception of manhood as a special-status category of achievement that requires indoctrination and testing. In order to account for the recent proliferation of the rituals, an attempt is made to situate them historically in the current context of contemporary ultraorthodox and Israeli society.